PERILAKU RELIGIUS TOKOH UTAMA NOVEL DZIKIR ILALANG (KUN FAYAKUN) KARYA ANDI BOMBANG - nurhandayani nurhandayani; muhammad fuad; kahfie nazaruddin (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
The problem of this study is how the protagonist’s religious behavior in the novel Dzikir Ilalang (Kun Fayakun) by Andi Bombang and its worthiness as a teaching material of literature in Senior High School are. This study aims to describe the protagonist’s religious behavior in the novel Dzikir Ilalang (Kun Fayakun) by Andi Bombang and to determine its worthiness as a teaching material of Indonesian literature in Senior High School. The method of this study is descriptive qualitative method. The source of data in this study is the novel Dzikir Ilalang (Kun Fayakun) by Andi Bombang. The result of the study shows that religious behavior of the protagonist in this novel, Hardi, covers five dimensions: ideology, worship, intellectual, physical, and experience. In the ideology dimension, the Hardi’s character has strong belief in Allah, His prophets, His Alquran, and His kodrat and iradat, and His Islamic doctrines. In the worship dimension, the religious behavior of Hardi’s character is realized in his behavior which is doing prayers, liking zikir (a kind of chant), and praying. In the intellectual dimension, the Hardi’s character has knowledge and comprehension about his religious tenets. In addition, in the phisycal dimension, his religious behavior is realized in his behavior which is polite and respectful to adults, modest, helpful, caring about, generous, gentle, thankful, full of affection, independent, just, never giving up, liking to associate, wise, responsible, humble (qonaah), honest, keeping promises, obedient, and sincere. And finally, the religious behavior of Hardi’s character in the experience dimension is realized in the religious experience which he has and feels. The novel Dzikir Ilalang (Kun Fayakun) by Andi Bombang is worthy to be teaching material alternative of Indonesian literature in Senior High School. This is based on the criteria of the literature teaching material selection which is considered from the aspects of literature and of character education. Seeing from character education, Hardi’s religious behaviour can be a material for characters education. One of his religious behaviour that can be material for education character is his polite and respect attitude to his parents.  Key words: religious behavior, intellectual, worship